An Exploratory Evidence of Youth’s ICT empowerment in Nigeria - Hafiz, Baba; Shaari Jamal, Abdul Nassir; Ibrahim Saleh, Adamu (Universiti Malaysia Sarawak, 2013)
The new ICT revolution has now broadened the horizon of the opportunities among nations, organization, institutions and individuals giving hopes to compete with their counterparts all over the world. It has been seen as an important vehicle to propel individual to greater height as the world moves further into the knowledge economy in this 21st century. It has been acknowledged that the information revolution is a powerful force with enormous benefits in socio-economic and political developments. Such benefits include job creation, increase in the stock of technologies and skills, ease of communication, expansion of trade, etc. particularly in developing countries. Against this background scale were source from literature and focus group analysis using 5 points likert scale. The questionnaire items have 65 indicators / constructs with the exception of demographic questions reflecting the relevant variables. An exploratory factor analysis was run on 389 valid responses from 3 geo-political zones in Bauchi state, Nigeria within the ages of 18-35 years. Using SPSS version 16 to check skewness and kurtosis. Utilising the maximum likelihood procedure which was followed by Varimax, rotation to get a better understanding of the factor structure.